Pursuing International Labour Rights in U.S. Courts: New Uses for Old Tools - Compa, Lance (Relations industrielles / Industrial Relations, 2002)
SummaryFiling lawsuits in U.S. federal and state courts for workers’ rights violations suffered by workers employed by American corporations abroad is one of several strategies for promoting labour rights. Other strategies include use of labour rights mechanisms in GSP laws, in regional trade agreements like NAFTA and Mercosur, in corporate codes of conduct, in the ILO and other venues. To succeed, such suits must first overcome the strong presumption against extraterritorial effect of U.S. law. Other jurisdictional hurdles like “inconvenient forum” also require caution in bringing suits. However, several cases using common law tort and contract theories as well as international human rights law have recovered substantial actual and punitive damages for workers of U.S. multinational companies in several developing countries. With the right strategic choices, labour rights litigation can be an effective means of advancing workers’ rights in the global economy.